Mutation of BRAF V600E in Iraqi Female Patients Diagnosed With Breast Cancer (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aimed to investigate the possible presence of BRAF V600E mutation in the Iraqi female patients who diagnosed with breast cancer in different ages, in which Blood and tissue samples were collected from 46 female patients with  age (46.73±3.54);Those were divided into two groups; who took chemotherapy (31 persons) as treated group and without chemotherapy as an untreated group (15 persons) and from (23) healthy person with age(47.93±3.05).  Polymerase chain reaction (PCR) were done with newly designed primers. The results revealed no correlation between breast cancer occurrence and BRAF V600E mutation in the Iraqi patients enrolled  in the current study.